A pilot psychological support group program for smoking cessation - Angelopoulou, Paraskevi; Maroglou, Foteini; Makrogianni, Christina (Psychology: the Journal of the Hellenic Psychological Society, 2020)
In the Prevention Center “Diktio Alpha”, a short-term group program of psychological support was developed to address the issue of smoking cessation at the local level in Thessaloniki. The aim of this study was to describe the application and effectiveness of the pilot psychological support group program as it was conducted by the Prevention Center. The program used an eclectic model, which was based on the Cognitive-Behavioural Therapy and Gestalt Therapy principles. Eight (8) two-hour focus group meetings were held from April until June 2016. The sample consisted of seven women (n=7) aged 37-59 years (M= 47.7 years). The participants’ level of nicotine dependence was measured through the use of Fagerström scale, where two people indicated low dependence, four medium dependence and one (person) high dependence. Data was codified and analyzed through the use of thematic analysis. According to the analysis, six broad thematic categories were formed: a) pre-thinking, how life was before the decision of cessation, b) thought or consideration of the decision to cease smoking, c) preparation for the cessation, d) action, e) maintaining of cessation, how life is after cigarette, and f) relapse. A follow-up call was conducted six months after the intervention, where three participants were found to having maintained smoking cessation. The results of this study could be used in the design and implementation of more intervention programs at a local level targeting vulnerable social groups.